Evaluation of Dosimetric Qualities of Ionization Chambers and Solid-State Detectors in Small Fields of a 60Co Teletherapy Unit - Akhter, Tanjina; Jamil, Hossen Mohammad; Rahman, Md Shakilur; Rubai, Sadeka Sultana; Meaze, AKM Moinul Haque; Sattar, Bushra Nafrin (Bangladesh Journal of Medical Physics, 2025)
Radiotherapy is a medical procedure that eliminates cancer cells by destroying their DNA. Secondary Standard Dosimetry Laboratories (SSDLs) serve an important role in providing traceable calibrations at certain radiation qualities for use in radiation measuring systems. The aim of this study is to investigate the absorbed dose rate to water (Dw) at the reference depth (zref = 5 g cm-2), the absorbed dose rate to water at the depth of dose maximum (Dmax), and the field output factors (OFs) for the different types of detectors (Farmer chamber type FC65-G, Semiflex chamber type 31010, Pinpoint 3D chamber type 31022, Diode E detector type 60017, and Microdiamond detector type 60019) in small fields of the 60Co teletherapy unit. The dosimetric performances were investigated for a reference field size of 10 × 10 cm2, and for small field sizes of 5 × 5 cm2, 4 × 4 cm2, 3 × 3 cm2, and 2 × 2 cm2. The measurements were conducted in a Blue Phantom2 3D water phantom according to IAEA dosimetry protocol TRS 398 coupled with an electrometer (Dose-1 electrometer), at a source to detector distance of 100 cm. The Dw (zref) values for all five detectors are decreasing as the field size decreases from 10 × 10 to 2 × 2 cm2. Response variance is significant among detectors below a field size 4 × 4 cm2. Output factors (OFs) decrease as field size decreases, with all five detectors responding the same from 10 × 10 cm2 to 5 × 5 cm2. However, at small field sizes less than 3 × 3 cm2, there is significant variation across these detectors. Solid-state detectors are more compatible with small field sizes, making the Microdiamond detector more appropriate. Ban. J. Med. Phys., Vol -16, Issue -2, 2025 : 37-43